Pressure wave propagation in the arterial system of the upper - Kizilova, N. (My University, 2004)
Pulse diagnosis method of the traditional oriental medicine gives an accurate and sensible tool for the early diagnosis of the whole body state, its regulatory systems and inner organ diseases, treatment prescribing, disease correction and prevention. Palpating the pulse of the radial arteries at the wrists and at other sites of the body is based on the consecutive compressions of the arteries and some pulse parameters estimation. A novel pulse diagnosis method that is based on the concept of the so-called resonant frequencies of the vascular beds of inner organs is proposed recently. Any changes in the parameters of intraorgan microcirculation cause noticeable alterations of the amplitudes of resonant harmonics of vasculatures with and without anastomoses. Reasonable biomechanical interpretation of the pulse diagnosis methods, more particularly the inner organ state diagnosis is absent at the moment.
Keywords: аrterial system; рulse diagnosis